ANALYSIS OF FACTORS AFFECTING THE WELL-BEING OF THE ELDERLY IN WEST DENPASAR DISTRICT - I Putu Yoga Sumakerta; Anak Agung Istri Ngurah Marhaeni (Adisam Publisher, 2025)
Elderly well-being is a form of respect for the contributions they have made to their families and communities throughout their lives. This study aims to analyze the factors affecting the well-being of the elderly in West Denpasar District. The sample size was determined using Slovin’s formula, resulting in 100 respondents, and the sampling techniques employed were accidental sampling and snowball sampling. Data were collected through a survey approach using questionnaires as the research instrument. The collected data were analyzed using multiple linear regression analysis. The results indicate that the well-being of the elderly falls into the high category, suggesting that, in general, the elderly in West Denpasar District experience a good level of well-being. Gender, employment status, marital status, family dependents, and family support simultaneously influence well-being in the district. Male elderly individuals have higher well-being than females, married elderly individuals have higher well-being than unmarried ones, and family support has a positive and significant effect on well-being. In contrast, employment status and family dependents have no significant effect on elderly well-being in West Denpasar District. Overall, the well-being level of both male and female elderly is high, with men having a slightly higher average than women.